Analysis of Android-Based Learning Media Needs in Information and Communication Technology Subjects - Romana Herlinda; Indri Astuti; Eny Enawaty (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this study is to analyze students' needs for Android-based learning media, especially for the basics of computer operation. The method used in this study is a qualitative method using the research topic of grade VII students of SMP N 8 Jangkang. This research uses the ADDIE learning design model, ADDIE itself is Analysis, Design, Development & Implementation, and Evaluation. It's just that the stage used in this study is only limited to the analysis stage. The instruments used are in the form of questionnaires for student needs and questionnaires for teacher needs. The data obtained in the study were then analyzed using a percentage formula. The results of the analysis show that 68% of the material on the Basics of Computer Operation is an applied subject, so that in the learning process it not only uses theoretical concepts but is also accompanied by practices that require students to be more independent so that learning media is needed so that it can be learned both in the form of e-modules (video, audio) so that it can be learned anywhere using android. The results of the analysis of the needs of 1 Information and Communication Technology teacher and 32 grade VII students showed that 90% of students had difficulty understanding the material. Based on the results of the study, it can be concluded that there is a need for the development of android-based interactive learning media on the material Basics of Computer Operation.